Packet loss and frame substitution techniques - Shah, Asadullah; Bhatti, Zeeshan (IIUM Press, 2011)
In packetized speech communication the packet loss occurs. The packets can also be forced to drop in situations when traffic load increase at the multiplexing end. The dropped packets can be substituted at the demultiplexing end. To do so frame substitution techniques can be utilised to mitigate the effects oflost packets. In this chapter packet loss (dropping) and frame substitution techniques are explained in detail